Development of Interactive Flipbook Based Teaching Materials on the Matter of Application of Norms in Life in Grade V Elementary School - Elpina, Elpina; Masniladevi , Masniladevi; Putera, Rafhi Febryan; Nisa, Sahrun (FKIP - Universitas Riau, 2025)
This research is motivated by the absence of interactive flipbook-based teaching materials in elementary schools. This study aims to develop teaching materials in the form of interactive flipbooks on the material of the application of norms in life in grade 5 elementary school. This research is a type of R&D (Research and Development) research. The development model used is the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The research data consists of qualitative data and quantitative data. The results showed that: 1) The results of the validity test by three validators obtained a percentage of 90% from material experts, 97.5% from media experts, and 82.5% from linguists with a very valid category. 2) The results of the practicality test showed an average percentage of teachers of 92.28% with a very practical category, and the and student practicality tests averaged 96.61% with a very practical category. Therefore it can be concluded that the development of interactive flipbook based on the topic of applying norms in life in grade v elementary school is very feasible to use in the learning process.